Emerging trends in the immunohistochemical characteristics of breast carcinomas in Uyo: A Niger-Delta region of Nigeria and a review of the literature - Emem Imo Akpanudo; Emmanuel Kunle Abudu; Ikwo Jonathan Kudamnya; Obioha Kanu; Oluwasayo Omolara Abudu (Hail Journal of Health Sciences, 2022)
Background: The quality of histological and immunohistochemical techniques dictate their usefulness in accurate diagnosis of breast cancer. Objectives: The study was set up to evaluate estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER2/neu) expressions in breast carcinomas by immunohistochemistry as well as ascertaining the correlation of these tumor markers with each other and their relationship with the ages of the patients in Uyo, a Niger-Delta region of Nigeria. Materials and Methods: A descriptive cross-sectional study using formalin-fixed paraffin-embedded tissue blocks of histologically confirmed cases of breast carcinomas over 5 years subjected to immunohistochemical analysis for ER, PR, and HER-2 as well as ascertaining correlation of these tumor markers with each other and their relationship with the ages of the patients were undertaken. Results: A total of 158 cases were analyzed. The mean age at diagnosis was 42.5 ± 3.5 years and the frequency of breast carcinoma peaked at the 41–50 years of age group and accounted for 42.4%. Invasive ductal carcinoma was the predominant tumor pattern (86.7%), with no special type (90.5%) and Grade 2 (56.9%) being the predominant characteristics. ER, PR, and HER-2 receptors were positive in 51.3%, 42.4%, and 12.0% of breast carcinomas, respectively. A subtype analysis of tumors showed that 48.7% were triple negative, peaking at the 31–40 years of age group with 51.3%. Positive correlation between ER, PR, and HER-2/neu as well as between tumor markers and patients' ages was recorded. Conclusion: Triple-negative breast carcinoma is still the predominant breast cancer subtype and occurs frequently in the 3rd decade of life.